2023
DOI: 10.1097/iae.0000000000003628
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Age-Related Macular Degeneration Showing a Poor Response to Three Loading Doses of Anti–vascular Endothelial Growth Factor

Abstract: To analyze the clinical features of refractory age-related macular degeneration patients associated with the response to three consecutive loading doses of anti-vascular endothelial growth factor.Methods: A retrospective chart review was performed on typical exudative age-related macular degeneration patients treated by three consecutive anti-vascular endothelial growth factor injections. The patients were divided into a group without residual fluid on optical coherence tomography images (Group 1) and a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…In our study, there were no significant factors associated with residual fluid following the three-injection loading phase based on baseline OCT characteristics. This contrasts with a previous study in which CT was significantly correlated with the presence of residual fluid after three loading anti-VEGF injections [ 10 ]. This discrepancy may arise from differences in inclusion criteria and anti-VEGF agents used between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, there were no significant factors associated with residual fluid following the three-injection loading phase based on baseline OCT characteristics. This contrasts with a previous study in which CT was significantly correlated with the presence of residual fluid after three loading anti-VEGF injections [ 10 ]. This discrepancy may arise from differences in inclusion criteria and anti-VEGF agents used between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…OCTA images at baseline and one month after final treatment were analyzed. Four criteria were adopted from previous studies to qualitatively describe a neovascular lesion in the images: the presence of tiny branching vessels (thin, tangled capillaries) as opposed to large mature vessels (voluminous linear filamentous capillaries); the presence of loops (internal anastomoses between tiny vessels); the presence of a peripheral arcade (connections between tiny branching vessels at the periphery); and the presence of a perilesional hypointense halo (hypointense area considered as regions of choriocapillaris alteration, corresponding to local flow impairment) [ 9 , 10 ]. To quantify MNV size, the two graders independently outlined the MNV lesion using internal software.…”
Section: Methodsmentioning
confidence: 99%
“…I read with interest the recent article by Song et al 1 entitled “Characteristics of Age-related Macular Degeneration Showing a Poor Response to Three Loading Doses of Anti–vascular Endothelial Growth Factor.” The authors compared the optical coherence tomography and optical coherence tomography angiography characteristics of eyes receiving three monthly loading doses of anti–vascular endothelial growth factor for neovascular age-related macular degeneration between eyes with “poor response” (residual fluid on optical coherence tomography 1 month after the third injection) and those with no residual fluid. Through univariate and multivariate analyses, they concluded that a thicker choroid on optical coherence tomography, and looping vessels and peripheral arcades on en face optical coherence tomography angiography are associated with a poor response to the three loading doses of anti–vascular endothelial growth factor.…”
mentioning
confidence: 99%
“…Through univariate and multivariate analyses, they concluded that a thicker choroid on optical coherence tomography, and looping vessels and peripheral arcades on en face optical coherence tomography angiography are associated with a poor response to the three loading doses of anti–vascular endothelial growth factor. 1…”
mentioning
confidence: 99%
“…We would like to thank Dr. Fouad of “RE: Characteristics of Age-Related Macular Degeneration Showing a Poor Response to Three Loading Doses of Anti–Vascular Endothelial Growth Factor” for their comments in response to our article. 1 We analyzed the baseline characteristics of optical coherence tomography (OCT) and OCT angiography (OCTA) of neovascular age-related macular degeneration (nAMD) patients according to the treatment response of 3-loading anti–vascular endothelial growth factor (anti-VEGF) injection. If any fluid was detected on OCT images, the patients were classified into Group 2, otherwise, the patients were classified into Group 1.…”
mentioning
confidence: 99%